Molecular Docking Study of Quercetin as an IGF1R Inhibitor for Anticancer Potential - Suryani, Puput Eka; Putri, Raden Roro Erni Kusuma; Mahanani, Annisah (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Cancer is one of the leading causes of death in the world and its incidence continues to increase every year. In 2024, there will be more than 20 million new cases of cancer with a death toll reaching 10 million people. This high mortality rate is a challenge in itself in developing effective, selective, and minimal side effect cancer therapies. One approach that is currently being widely developed is therapy based on suppressing the cancer cell growth signal pathway, one of which is through inhibition of the Insulin-like Growth Factor 1 Receptor (IGF1R) receptor which is known to play an important role in proliferation, metastasis, and resistance to cancer therapy. From several experiments based on quercetin as an IGF1R inhibitor, there has been no explanation whether quercetin is capable of being an IGF1R inhibitor agent at the intracellular level. This study aims to evaluate the role of quercetin on the kinase domain and its activity at the ATP-binding site in silico through the molecular docking method. Based on the results of the study, it was concluded that quercetin is capable of acting as an IGF1R protein inhibitor. This was confirmed by several bonds formed between residues Val331A, Asp292A, Glu294A, Ser287A through hydrogen bonds with quercetin